2013
DOI: 10.1042/cs20120644
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells derived from adipose tissue reduce functional and tissue damage in a rat model of chronic renal failure

Abstract: Therapeutic approaches for CKD (chronic kidney disease) have been able to reduce proteinuria, but not diminish the disease progression. We have demonstrated beneficial effects by injection of BM (bone marrow)-derived MSCs (mesenchymal stem cells) from healthy donors in a rat model with CKD. However, it has recently been reported that BM-MSCs derived from uraemic patients failed to confer functional protection in a similar model. This suggests that autologous BM-MSCs are not suitable for the treatment of CKD. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 57 publications
0
46
0
4
Order By: Relevance
“…Importantly, these attributes of hemin were accompanied by the restoration of adipocyte morphology and improved adipocyte function as evidenced by increased adiponectin levels. Given that hypertriglyceridemia, hypercholesteromia, and excessive pericardial adiposity are major pathophysiological causes of heart failure and related cardiac complications, 8,[43][44][45][46] the suppression of hypertriglyceridemia, hypercholesteromia, and pericardial adiposity in hemin-treated ZFs, and the corresponding decline of adipocyte hypertrophy, TGF-b, osteopontin, pro-inflammatory macrophage M1 phenotype, TNF-a, IL-6, IL-1b, and 8-isoprostane, [22][23][24][25][26][27][28][29][30][31]54,[60][61][62][63] which were associated with the potentiation of the anti-inflammatory macrophage M2 phenotype, proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] are among the multifaceted mechanisms by which the HO system restores adipocyte morphology and improved adipocyte function. Moreover, the effect of the HO system on the expression of proteins of regeneration such as Oct3/4 and pax2 is a novel mechanism unveiled by this study through which hemin may restore adipocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these attributes of hemin were accompanied by the restoration of adipocyte morphology and improved adipocyte function as evidenced by increased adiponectin levels. Given that hypertriglyceridemia, hypercholesteromia, and excessive pericardial adiposity are major pathophysiological causes of heart failure and related cardiac complications, 8,[43][44][45][46] the suppression of hypertriglyceridemia, hypercholesteromia, and pericardial adiposity in hemin-treated ZFs, and the corresponding decline of adipocyte hypertrophy, TGF-b, osteopontin, pro-inflammatory macrophage M1 phenotype, TNF-a, IL-6, IL-1b, and 8-isoprostane, [22][23][24][25][26][27][28][29][30][31]54,[60][61][62][63] which were associated with the potentiation of the anti-inflammatory macrophage M2 phenotype, proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] are among the multifaceted mechanisms by which the HO system restores adipocyte morphology and improved adipocyte function. Moreover, the effect of the HO system on the expression of proteins of regeneration such as Oct3/4 and pax2 is a novel mechanism unveiled by this study through which hemin may restore adipocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the mechanisms by which hemin improves pericardial adipocyte morphology, we measured the expression of proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] in the adipose tissue. Our results indicate that the expressions of beta-catenin, Oct3/4, and pax2 in ZFs were significantly reduced as compared to the ZL control (Figure 7(a) to (c)).…”
Section: Hemin Administration Enhanced Proteins Of Regeneration In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have hypothesised that certain growth factors or specific hormones, including HGF, EGF and IGF-1, are able to promote this transformation process, and accelerate the differentiation of nascent epithelial cells (30)(31)(32). In addition, several scholars have demonstrated that BMSCs are able to secrete a number of cytokines, thereby promoting the proliferation and repair of the endogenous renal tubular epithelial cells (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs from various sources (such as bone marrow, fetal membrane and adipose) in repairing kidney injury were reported, [2][3][4] however, the potential immune rejection, adipogenic differentiation and malignant transformation events of MSCs limit our clinical use. EVs contained in the MSC's condition medium could repair variety injured organs and also could alleviate I/R injury induced AKI.…”
Section: Introductionmentioning
confidence: 99%